Pengaruh Kualitas Produk Dan Harga Terhadap Tingkat Penjualan Dengan Kualitas Pelayanan Sebagai Variabel Intervening Pada House Of Smith Padang - Ramadhan, Muhammad Fikri; Yamasitha; Mayang Sari, Fitri Indah (Riset Sinergi Indonesia, 2024)
This study aims to determine how much influence product quality and price have on sales levels with service quality as an intervening variable for House Of Smith consumers. The method used is Structural Equation Modeling (SEM) with Partial Least Square (PLS) 3.0. By distributing questionnaires to 100 respondents. The results of the data analysis concluded that there was a positive and not significant effect of the product quality variable on the service quality variable. There is a positive and significant effect of the price variable on the service quality variable. There is a positive and significant effect of the product quality variable on the sales level variable. There is a positive and insignificant influence on the level of sales. There is a positive and significant influence of service quality variables on sales level variables. There is a positive and not significant effect of the product quality variable on the sales level variable with the service quality variable as the intervening variable. There is a positive and significant effect of the price variable on the sales level variable with the service quality variable as the intervening variable.